Cine y casi cine. (Madrid : MNCARS (Museo Nacional Centro de Arte Reina Sofia) Madrid, 2007)
Akerman, Chantal ; Asdam, Knut ; Barber, George ; Berkowitz, Hisham ; Bizri, Hisham ; Boutet, Antoine ; Cabello, Helena ; Carceller, Ana ; Cohene, Aleesa ; Devic, Goran ; Dutta, Amit ; Esquivias, Patricia ; Finn, Jim ; Fogarasi, Andreas ; Forsyth, Iain ; Garcia, Dora ; van der Horst, Aliona ; Islam, Runa ; Jodice, Francesco ; Kleinjan, Arthur ; Lorenz, Claudia ; Marina, Hernan ; Masharawi, Rashid ; Maté, Mateo ; Meessen, Vincent ; Muntadas, Antoni ; Narkevicius, Deimantas ; Odenbach, Marcel ; Pietsch, Oliver ; Pollard, Jane ; Price, John ; Rooney, Paul ; Rosefeldt, Julian ; Schlüters, Eske ; Schmidt, Erik ; Schreiner, Volker ; Schweizer, Maya ; Sun Xun ; Tan, Fiona ; Terziev, Krassimir ; Vassileva, Mariana ; Wedemeyer, Clemens von ; Wilcox, T.J. ; Wojtasik, Pawel ; Zhao Liang
biog. p. 48-57
Spaans
Exhibition. Cine y casi cine. MNCARS (Museo Nacional Centro de Arte Reina Sofia) Madrid. 05.11.2007 - 17.12.2007
boek